Experiences of nursing professionals in alternative and complementing therapies applied to people in pain situations Experiencias de profesionales de enfermería en terapias alternativas y complementarias aplicadas a personas en situaciones de dolor - MARÍN ARIZA DIEGO ANDRÉS; FORERO ARCHBOLD ANDRÉS; LARA SUÁREZ PAOLA MILENA; CALDERÓN PERILLA ARNOL YAMID; VANEGAS DE AHOGADO BLANCA CECILIA; CELIS RINCÓN ADRIANA (Universidad Nacional de Colombia, 2008)
To know the experiences of nursing professionals on the use of alternative and complementing therapies applied during health care to people in pain situations, a qualitative study was carried out, as a graduation project for a group of nursing students -undergraduates- from the Universidad del Bosque, between 2005 and 2007, in which four nursing professionals took part. They had several years of experience in the use of floral therapy, acupuncture, homeopathy, chiropractic massage therapy and naturopathy; in other words, those therapies that also enable a synergic action when combined with the conventional therapeutic medical-pharmacologic-surgical procedures, which they complement; the selection of participants wasmadeusing the "snow ball" technique. The information was gathered by means of semi-structured deep interviews. The analysis of the results enabled us to learn that said experiences do not have as sole purpose to relieve a determined type of pain, but, generally, to evaluate the health condition and to intervene with an integral focus, considering the individual as a holistic human being; on the other hand, this work has given the students great satisfaction and possibilities for personal development. Para conocer las experiencias de profesionales de enfermería en el uso de terapias alternativas y complementarias aplicadas durante el cuidado de la salud a personas en situación de dolor, se realizó un estudio cualitativo, como trabajo de grado de un grupo de estudiantes -de pregrado- de Enfermería de la Uni-versidad El Bosque, entre los años 2005 y 2007, en el que participaron cuatro profesionales de enfermería, con varios años de experiencia en la utilización de Terapia Floral, Acupuntura, Homeopatía, Quiromasaje y Naturopatía; es decir, aquellas terapias que, además permiten una acción sinérgica al combinarse con los procedimientos terapéuticos médico-farmacológicos-quirúrgicos convencionales, a los cuales complementan; la selección de participantes se hizo mediante la técnica de bola de nieve. La información se recogió a través de entrevistas profundas semiestructuradas. El análisis de los resultados, permitió conocer que dichas experiencias no tienen como único propósito aliviar determinado tipo de dolor, sino, por lo general, valorar el estado de salud y hacer las intervenciones con enfoque integral, considerando a la persona como un ser holístico; por otra parte, este trabajo les ha proporcionado a las participantes gran satisfacción y posibilidades de desarrollo personal.